Evaluación de un Sistema de Riego por Aspersión en un predio del sector El Porvenir, parroquia Malacatos - Abad Ludeña, Cinthia Estefanía (2023)
The investigation was carried out in the El Porvenir area, which is part of Board No.1 of the Campana-Malacatos irrigation system, to assess the effectiveness of sprinkler irrigation on a property to improve the uniformity and efficiency of irrigation. To characterize the irrigation methods used in the region, a survey was conducted with 75 users. The results indicate that the primary agricultural activities in the area are subsistence and commercial agriculture, the 65% of users owning land areas smaller than 1 hectare. In the study area, sprinkler irrigation accounts for 59%, while gravity irrigation accounts for 41%. The property covers an area of 0.3 hectares, with texture soil loam, an apparent density of 1.35 g/cm3, moisture content at a saturation of 33.8%, Field Capacity of 27.8%, and a permanent wilting point of 9.4%. The water for irrigation presented a slightly alkaline pH of 7.6, and its salinity is 0.030 dS/m of CE. The sodium absorption ratio is 1.71, and suspended solids are 282.00 mg/l. These water quality parameters are within acceptable ranges; therefore, they do not present a restriction of use. In the evaluation and the hydraulic operation of the system, it presented deficiencies in its design, components in poor condition that affect the correct operation, the Christiansen uniformity coefficient was 85%, the distribution and installation uniformity were unacceptable of 70% and 63% correspondingly, the losses by evaporation and dragging of the wind of 22.61%, the thickness index of the drop was 10.81 and 18.01. Based on the results, the irrigation redesign was carried out, the reference evapotranspiration (ETo) was calculated with the Hargreaves method, by obtaining meteorological data from the stations of Quinara, Yangana and Malacatos with a series of 23 years (1990 - 2013), determining that it should be irrigated with a frequency of 8 days and a time of 8 hours to compensate the irrigation sheet for the coffee that is 46.00 mm, using the NETAFIM 9575 sprinkler. The hydraulic design of the irrigation system defined the primary, secondary, and tertiary (irrigation lateral) pipe networks, with diameters of 75, 63, respectively. According to the results of the evaluation and the redesign, it will be possible to improve the irrigation system, with a view to having a better uniformity in the application of irrigation water and, thus, using water resources efficiently. Keywords: irrigation evaluation, sprinkler irrigation, distribution efficiency, irrigation uniformity, coffee growing.